CARA GURU DALAM MENGEMBANGKAN BUTIR TES PILIHAN GANDA SEBAGAI INSTRUMEN EVALUASI HASIL BELAJAR - Efrina, Gustina; Nengsi, Ayu Rahma; Oktira, Yona Syaida (Inspiratif Pendidikan, 2021)
The low quality of teacher-made tests makes the information provided by the measurement results of these tests doubtful as a basis for educational decision making. In order to clearly identify the cause of the low quality of the test, it is important to conduct research that aims to look deeper into the methods that teachers take in the process of developing tests in the field. The sample was taken purposively, limited to 4 teachers at six grade, who were involved in the UTS and UAS question preparation team in Lubuk Alung District. The triangulation technique was chosen for data collection, the four samples were observed several times until the question writing process was completed. Interviews were conducted on matters that were not clear to the researcher during the process. Photos, videos and the form of test instruments made required was collected as documentations. The research findings show that basically the teacher has followed a part of the flow, although not all of the steps were followed correctly during the test item writing process. The findings of the study indicate the process of writing the items by the teacher, namely 1) the design of the lattice table, 2) the writing of the items was found: a) the choice of the operational words only measured aspects of knowledge and understanding, b) there were many negative types of questions such as the use of the word 'except' , c) the distractor is made very predictable, d) there is an ambiguous question language 3) the test review is carried out by a special team who edits all tests before they are printed and distributed, 4) testing and analysis of grain quality is not carried out at all, due to limitations funds, time and effort.